How do Clinicians Use Electronic Health Records for Respiratory Support Decisions? A Qualitative Study in Critical Care - Zhang, Tianyi; Mosier, Jarrod; Subbian, Vignesh (ACI Open, 2025)
Objectives Selecting appropriate respiratory support in critical care is complex, and some decisions require information that may be unknown when the treatment assignment is necessary. Digital technologies such as electronic health records (EHR) are essential components in critical care medicine to support respiratory support care delivery and management of patients with respiratory failure. However, there are limited studies on EHR use that enable clinical decisions related to respiratory support. The objective of this study is to understand how clinicians use EHRs for their decision-making related to respiratory support in intensive care units (ICUs).Methods Using a socio-technical systems approach, we conducted nine observations with nine different care teams for 35 hours at two ICUs within a large academic hospital system. We created a journey map to illustrate clinicians' respiratory support decision-making processes. We identified barriers related to decision-making processes within the ICU socio-technical work context and characterized them based on macro-cognitive functions to derive themes that can capture the decision-making patterns associated with EHR use.Results Our analysis identified three overarching themes that represent clinicians' use of EHR for their respiratory support decisions: (1) fragmented information and tasks for individual sensemaking; (2) EHR workarounds for collaborative decision-making; and (3) interruptive order entry and order execution. These three themes represent three major sequential stages (i.e., before, during, and after morning rounds) related to clinicians' respiratory support decision-making processes, and their interaction with EHR significantly varies between stages.Conclusion Our findings reflected different EHR use patterns before, during, and after morning rounds for decision-making related to respiratory support. These findings indicated potential opportunities for diagnostic clinical decision support (CDS) to facilitate respiratory support decisions.
Keywords: electronic health record; critical care; respiratory support; clinical decision support; qualitative study